2011
DOI: 10.1126/science.1202357
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemically Mediated Atom Transfer Radical Polymerization

Abstract: Atom transfer radical polymerization is a versatile technique for exerting precise control over polymer molecular weights, molecular weight distributions, and complex architectures. Here, we show that an externally applied electrochemical potential can reversibly activate the copper catalyst for this process by a one-electron reduction of an initially added air-stable cupric species (Cu(II)/Ligand). Modulation of polymerization kinetics is thereby tunable in real time by varying the magnitude of applied potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
652
0
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 750 publications
(665 citation statements)
references
References 32 publications
6
652
0
7
Order By: Relevance
“…18 Our own work has demonstrated that activation may be driven electro-catalytically. 19 Figure 1) the weakly bound axial solvent ligand is easily displaced (broken lines, Figure 1).…”
Section: Introductionmentioning
confidence: 98%
“…18 Our own work has demonstrated that activation may be driven electro-catalytically. 19 Figure 1) the weakly bound axial solvent ligand is easily displaced (broken lines, Figure 1).…”
Section: Introductionmentioning
confidence: 98%
“…In the past few years, several modified ATRP techniques have been developed that enable the synthesis of well-defined (co)polymers using very low concentrations of copper catalyst (1-200 ppm). Among these, initiators for continuous activator regeneration (ICAR) [15] and activator regenerated by electron transfer (ARGET) [16][17][18] ATRP and the recently developed electrochemically mediated ATRP [19] (eATRP) techniques can have a significant impact on the industrial applicability of ATRP.…”
Section: Introductionmentioning
confidence: 99%
“…Even though selection of the appropriate ATRP catalyst enables the synthesis of well-defined polyacrylates and purification methods are available for its removal, [37][38][39][40][41] the amount of catalyst in a normal ATRP process is too high to obtain an economic profitable process. [1,42] Therefore, in the last years, ATRP modified techniques [5,[43][44][45][46][47][48][49][50][51][52][53][54] have been developed in which a low catalyst concentration (ppm level with respect to monomer) is employed. Importantly, these techniques can be applied using commercially available ligands, are more environmentally friendly and avoid the oxygen sensitivity of the activator upon storage.…”
Section: Introductionmentioning
confidence: 99%